UNDERGRADUATE STUDENTS’ PERCEPTION OF THE FACTORS THAT INFLUENCE ADOPTION OF HOMOSEXUALITY IN SELECTED PUBLIC UNIVERSITIES IN KENYA. - OMONDI, ALICE WAIRIMU OMONDI (KABARAK UNIVERSITY, 2016)
Homosexuality is a behavior involving sexual attraction between people of the same sex. Homosexuality is a problem in universities and complaints of its existence in universities have been raised and some university students have even declared publicly about their sexual orientation. Those who have adopted homosexuality may have been influenced by factors such as inadequate counseling, mass media, religious affiliation and peer pressure. Therefore, the purpose of the study was to establish undergraduate students’ perception of the factors that influence adoption of homosexuality in selected public universities in Kenya. The study also aimed at determining gender differences in students’ adoption of homosexuality. Social Cognitive Theory of Albert Bandura guided the research. The study was carried out among third year undergraduate students in selected public universities in Kenya. These universities were Egerton University, Moi niversity, University of Eldoret and University of Kabianga. Third year undergraduate students were chosen because they had been in the university for long and understood well the factors influencing students to adopt homosexuality. They had also been in the university longer and may have developed some perception towards the factors influencing adoption of homosexuality. The study adopted an ex post facto research design. The target population was fifty-three thousand (53,000) undergraduate students. The accessible population was twelve thousands and three hundred (12,300) third year undergraduate students. Out of this population, a sample of 225 was selected through stratified random sampling and simple random sampling. The study also included a sample of forty (40) peer counselors and four (4) university counselors from the four universities who were selected through purposive sampling. Data collection instruments were questionnaire, an interview schedule and a focus group discussion guide. Validation of the research instruments was done through peer and expert review and also through pilot testing. Cronbach alpha coefficient was used to establish reliability of the questionnaire. Reliability coefficient of 0.883 was obtained which is above 0.7 that is recommended. The data obtained was analyzed using both descriptive and inferential statistics with p value set at 0.05. The findings revealed that gender differences in students’ adoption of homosexuality do not exist. Further findings indicated that majority of the respondents were of the view that mass media influences adoption of homosexuality. The study recommends that measures on how best to handle homosexuality issues should be targeted at all students because homosexuality cuts across gender. The study also recommends that media owners and the government regulate programmes that might influence students to adopt homosexuality.
FULL TEXT
Keywords: Undergraduate Students, Perception of the Factors, Adoption of Homosexuality and Selected Public Universities.